DIGITALISASI FILANTROPI ISLAM: STUDI PENGGUNAAN QRIS DALAM PENGUMPULAN DANA ZAKAT INFAK SEDEKAH (ZIS) DI MASJID-MASJID DI KOTA GORONTALO - Rahman, Supandi; Lasena, Rahmawati (Journal of Principles Management and Business, 2024)
This study explores the implementation of QRIS (Quick Response Indonesian Standard) as an innovative solution to enhance the collection of Zakat, Infaq, and Sedekah (ZIS) funds in mosques across Gorontalo City. Employing a qualitative descriptive method, the research gathers data through interviews, observations, and documentation, utilizing both primary and secondary sources. The analysis follows the Miles and Huberman model, encompassing data collection, reduction, presentation, and conclusion/verification. The findings reveal that the adoption of the QRIS digital payment system reflects an effort by mosque management to embrace technological advancements and improve the efficiency of ZIS collection. Among the five mosques studied, two have demonstrated effective implementation, while the other three face challenges that hinder optimization. The convenience of cashless donations through smartphones has primarily attracted younger generations, highlighting the potential for increased engagement in digital giving. However, significant challenges remain, including limited public awareness and technical obstacles such as network instability. Addressing these issues through targeted outreach and improved infrastructure could further optimize the role of QRIS in modernizing the financial management of mosques and strengthening community participation in ZIS contributions.